Quality of wheat silage produced under different levels of nitrogen dressings at two phenological stages (Revista de Ciências Agroveterinárias, 2018)
The objective was to evaluate the effects of two content levels of nitrogen dressing (88 kg ha-1 and 148 kg ha-1) in the wheat silage production of BRS Umbu harvested during two phenological stages (pre-flowering and floury grain). The production of fresh dry phytomass as well as morphological and chemical composition of silages were evaluated. This study used a randomized blocks design with a 2x2 factorial structure, with two content levels of nitrogen dressing and at two different harvest stages, with four replications. There was interaction (p
Keywords: preserved food; neutral detergent fiber; floury grain; pre-flowering; crude protein